Measuring Sea Level with GPS-Equipped Buoys: A Multi-Instruments Experiment at Aix Island - André, Gaël; Martín Míguez, Belén; Ballu, Valérie; Testut, Laurent; Wöppelmann, Guy (The International Hydrographic Review, 2013)
Measuring sea-level in a global reference frame with sub-centimeter accuracy is a relevant challenge in the context of current global warming and associated sea-level rise. Global Navigation Satellite Systems (GNSS) can provide sea-level measurements directly referenced in an absolute geocentric frame. We present here the results of a multi-instruments experiment with three buoys equipped with Global Positioning System (GPS), a radar tide gauge and a tide pole. This experiment was carried out at Aix Island (West coast of France) on the 27-28 March 2012. The GPS buoys were evaluated against conventional tide gauge measurements through a Van de Casteele test. The Root Mean Square Error (RMSE) computed from the difference between the GPS-buoys and radar tide gauge data ranges from 1 cm to 2.2 cm, which is suitable for tidal applications and offers interesting perspectives for future sea-level variations studies.